Obligation d’information du professionnel en droit Algérien - Belabed, Toufik (Journal of Human Sciences, 2022)
The purpose of the obligation to inform is to enlighten the consumer and enable him to acquire the product or the provision of a service in complete transparency, given that he can only determine the essential characteristics of the product and its components on the basis of the data communicated to him. The legislator has prescribed this obligation in the provisions of common law, in an ambiguous manner and which he considers as a general guarantee for the consumer, without it aiming to protect the consumer, which has led French case law to impose the duty advice, hence the need for the existence of a separate right to consumption, the purpose of which will be to protect the consumer through the obligation to inform, which is only compulsory labelling.